A partially linear approach to modelling the dynamics of spot and futures prices - Jürgen Gaul; Erik Theissen (Goethe University Frankfurt, Center for Financial Studies (CFS), 2008)
In this paper we consider the dynamics of spot and futures prices in the presence of arbitrage. We propose a partially linear error correction model where the adjustment coefficient is allowed to depend non-linearly on the lagged price difference. We estimate our model using data on the DAX index and the DAX futures contract. We find that the adjustment is indeed nonlinear. The linear alternative is rejected. The speed of price adjustment is increasing almost monotonically with the magnitude of the price difference.
urn:nbn:de:hebis:30-54405
Keywords: C32; C14; G13; G14; 330; Futures Markets; Cointegrated Systems; Partially Linear Models; Nonparametric Methods; Börsenkurs; Aktienindex; Index-Futures; Arbitragegeschäft; Kointegration; Partial-Least-Squares-Modell; Nichtlineares Verfahren; Schätzung; Theorie; Deutschland